MENINGKATKAN KEMAMPUAN MEMBACA DENGAN STRATEGI MEMBACA KWL (KNOW, WHANT TO KNOW AND LEARND) SISWA KELAS X MPLB A SMK NEGERI 1 SINGARAJA TAHUN 2022/2023 - Ni Nyoman Murtini (Daiwi Widya, 2022)
AbstractThis classroom action research was carried out with the aim of improving students’ reading skills. The low initial data acquisition of class X MPLB A students at SMK Negeri 1 Singaraja in the odd semester of the Academic year 2021/2022 has prompted researchers to try to increase the poor processes that have been implemented. Improving the learning process was carried out through the implementation of the KWL (Know, What to Know and Learned) strategy. This strategy was expected to solve the problems being faced. After the data was collected through the learning achievement test instrument, it was obtained an increase in reading ability with the initial data which the class average reached 76.45 with 77.41% for learning completeness. Whereas in cycle II, the data has increased to 84.67 for the class average and 96.77% for learning mastery. The data in Cycle II have shown the successful implementation of learning that exceeded the required indicators. Therefore, the researcher concluded that the implementation of the KWL (Know, What to Know and Learned) strategy in carrying out the learning process was able to improve students’ reading skills.Keywords: implementation of the KWL (Know, What to Know and Learned) strategy, reading ability